The death of Scripture and the rise of biblical studies - Legaspi, Michael C. (Oxford ; New York : Oxford University Press, 2010)
The Bible has always been a contested legacy, and during the Enlightenment, Europe's scriptural inheritance surfaced once again at a critical moment as scholars guided by a new vision of a post-theological age remade the Bible. In place of the familiar scriptural Bibles that belonged to Christian and Jewish communities, they created a new form: the academic Bible. In this book, Michael Legaspi examines the creation of the academic Bible. Beginning with the fragmentation of biblical interpretation in the centuries after the Reformation, Legaspi shows how the weakening of scriptural authority in the Western churches altered the role of biblical interpretation. In contexts shaped by skepticism and religious strife, interpreters increasingly approached the Bible as a text to be managed by critical tools. These developments prepared the way for scholars to formalize an approach to biblical study oriented toward the statist vision of the new universities and their sponsors. Focusing on renowned German scholar Johann David Michaelis (1717-1791), Legaspi explores the ways in which critics reconceived the role of the Bible. The founders of modern biblical criticism preserved the cultural authority of the Bible by creating an institutional framework for biblical interpretation designed to parallel--and replace--scriptural reading. This book offers a new account of the origins of biblical studies, illuminating the relation of the Bible to churchly readers, theological interpreters, academic critics, and people in between. It explains why, in an age of religious resurgence, modern biblical criticism may no longer be in a position to serve as the Bible's disciplinary gatekeeper.
From Scripture to text -- Bible and theology at an Enlightenment university -- The study of classical antiquity at Göttingen -- Michaelis and the dead Hebrew language -- Lowth, Michaelis, and the invention of biblical poetry -- Michaelis, Moses, and the recovery of the Bible.
Includes bibliographical references and indexes.
Keywords: Michaelis, Johann David, -- 1717-1791.; Bible. -- Criticism, interpretation, etc. -- History